The Path of Digital Government and University Asset Intelligence Value-Added Service Driven by Block Chain Technology. (29th May 2022) - Feng, Qian; Mohd Ramli, `Razlini; Liu, Youwu
Abstract : At present, the government and universities mainly adopted the centralized management mode in the sharing of asset digital resources, which not only had low work efficiency, but also cannot make full use of resources. Block chain technology played an important role in enterprise asset data resource data sharing, but there was less research on asset data sharing services applied to digital government and universities. Therefore, this paper proposed the research on the path of government and university asset value-added service driven by block chain technology, in order to provide reference for improving the utilization rate of state-owned assets and better meeting the needs of users. Based on the research on the problems existing in the digital resource management of relevant government agencies and university departments at home and abroad, combined with the application advantages of block chain technology in relevant fields, this paper analyzed the composition of block chain and the application technical characteristics of value-added services. Starting from the current situation of asset data information management by the government and universities and the needs of users for resources, this paper expounded the important impact of block chain technology on digital government and university asset information management. By analyzing the elements of block chain value-added service, this paper put forward the block chain-driven asset intelligent value-added service mode. In order to track and manage users' transaction information and meet users' demand for resources, the application path of asset intelligent value-added service driven by block chain technology was constructed based on the asset value-added service mode, and combined with the characteristics of users' request for resources, the implementation method of asset intelligent value-added service path was proposed. The experimental results showed that the method proposed in this paper had more advantages than the existing data sharing service system, and can effectively provide technical support for asset value-added services.